Community participation in the establishment of community policing forum : a case study of Nelspruit Police Station, Mpumalanga Province - Nkwenyane, Evelyn Badiketlile (My University, 2011)
Participation of members of the community in policing is critical in ensuring that policing becomes a people oriented process. This will go a long way into a ensuring that a shift in the policing environment, from a police force to a police service underpinned by involvement of community members in policing activities is realised throughout South Africa. That is, since 1993, the South African Police Service (SAPS) adopted a community policing process to meet the safety and security requirements of all people in the country. A major objective of community policing is to establish active partnership between the police and the community, especially at local level through which crime, service delivery and community-police relations can be evaluated and plans to address problems implemented. Throughput South Africa, Community Policing Forums (CPF) has been set up to work with SAPS. This study was conducted with the aim of establishing the extent to which communities around the Nelspruit policing area, in the Mpumalanga Province, participate in the establishment of the existing Community Policing Forums (CPFs), to sought means and ways through which there can be maximal involvement or participation in community policing around the Nelspruit Policing Area.Accordingly, Mpumalanga as a province has also adopted community policing as a strategy towards ensuring better policing. Police stations have been mandated to establish CPFs in consultation with relevant stakeholders and communities. The establishment of community policing forums and boards, which should be broadly representative of the community, is of crucial importance. The main objective of partnership is to determine, through, consultation, community needs and policing priorities, and to promote police accountability, transparency and effectiveness. The research methodology used for the study was a combination of both qualitative and quantitative research design. This enabled the researcher to draw data from the identified sample of study, in order to respond to critical research questions as raised in Chapter 1 of the study. As a result the study was divided into five (5) Chapters ssummarised as follows: Chapter 1 of this study introduces the study by presenting the research problem, aim and objectives of the study, research questions, and division of the study; and Chapter 2 of the study presents literature review. In other words, chapter 2 examines selected empirical research, reported practice and identified innovations relevant to community participation in the community policing forum (CPF). It provided the study with an opportunity to give better insight into the dimensions and complexity of the problem. Chapter 3 of the study presents Research Methodology used in the study. In the main chapter 3 expatiates on the necessary tools employed in the study to elicit the necessary research outcome. This includes research design, data collection method, data analysis, and interpretation. On the other hand, Chapter 4 of the study presents observations drawn from the data as presented, this done in order to describe and explain community participation in CPF within the Nelspruit Policing Area, in Mpumalanga Province of South Africa. Lastly, Chapter 5 in the main presents recommendations and conclusions drawn from the study. The following were findings of the study: lack of public awareness on the CPF and its activities; unclear or undefined roles and responsibilities on members of the community in CPFs; lack of proper resources to carry out the work of CPFs by community members, underrepresentation of previously disadvantaged groups and organized groups in CPFs It is recommended that efforts need to be put in place to increase public awareness on the CPF via print and electronic media; CPFs must be provided with budget, offices, transport, computers, resources aimed at ensuring visibility of CPF members in communities (reflector jackets, and enabling resources - torches , whistles), and communication technology; allocation of roles and responsibilities to members of the community partaking in CPFs shall help to dispel the thinking that community members are only used as tokens or spies for SAPS, and instil a feeling of ownership of policing by community members; and a special focus needs to be put in place to encourage members of the community and CPFs to engage individuals drawn from previously disadvantaged groups and organised groups for increased participation in CPFs by this groups.
Thesis (MPA.) --University of Limpopo,2011
Keywords: Community participation; Community policing forum; 363.230968; Community policing